Kromatografi Lapis Tipis Video Densitometri sebagai Alternatif Analisis Simultan Rifampisin dan Isoniazid dalam Sediaan Kombinasi - Fauzan Zein; Yusril Panji; Deden Indra Dinata (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2026)
Rifampicin and isoniazid are first-line antituberculosis drugs widely used in tuberculosis therapy. Simultaneous determination of both compounds is required to ensure the quality and safety of pharmaceutical preparations. This study aimed to develop a Thin-Layer Chromatography (TLC) Video Densitometry method as an alternative approach for the simultaneous analysis of rifampicin and isoniazid in combination tablets. Separation was performed using silica gel GF254 as the stationary phase and methanol:ammonia (10:1) as the mobile phase. Spot visualization was carried out under UV light at 254 nm and analyzed using ImageJ software to obtain the area under curve (AUC) values. Method validation included selectivity, linearity, sensitivity, accuracy, and precision tests. The results showed that the Rf values of rifampicin and isoniazid were 0.78 and 0.66, respectively, with a selectivity factor of 1.18. The calibration curves demonstrated good linearity with determination coefficients of 0.9987 for rifampicin and 0.9992 for isoniazid. The recovery values ranged from 99.20–99.70% for rifampicin and 99.56–99.80% for isoniazid, while the %RSD values were less than 2% for both compounds. The assay results of combination tablets showed rifampicin levels of 82.42–82.46% and isoniazid levels of 78.00–78.47%. Based on the validation results, the TLC video densitometry method fulfilled the validation parameters and can be used as an alternative method for the simultaneous analysis of rifampicin and isoniazid in combination preparations.